2013
DOI: 10.3762/bjnano.4.30
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopic surfactant behavior of the porin MspA in aqueous media

Abstract: SummaryThe mycobacterial porin MspA is one of the most stable channel proteins known to date. MspA forms vesicles at low concentrations in aqueous buffers. Evidence from dynamic light scattering, transmission electron microscopy and zeta-potential measurements by electrophoretic light scattering indicate that MspA behaves like a nanoscale surfactant. The extreme thermostability of MspA allows these investigations to be carried out at temperatures as high as 343 K, at which most other proteins would quickly den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…x = 0 is the position of MspA’s constriction along the ssDNA when the NeutrAvidin is pulled against the entrance to the pore’s vestibule, and x = L domain is the position of MspA’s constriction along the ssDNA when the end of the ssDNA tail escapes from the constriction altogether. By considering the length of DNA(19) and the total size of the MspA pore(6, 20), L domain is set to be the length of 14 nucleotides, with length per base a 0 =0.5nm. According to the first-passage approach, we define the probability of passage times as f esc ( x 0 , t ) dt , which represents the probability that the DNA escapes from the pore back into solution within a time between t and t + dt, given an initial starting position x 0 .…”
Section: Resultsmentioning
confidence: 99%
“…x = 0 is the position of MspA’s constriction along the ssDNA when the NeutrAvidin is pulled against the entrance to the pore’s vestibule, and x = L domain is the position of MspA’s constriction along the ssDNA when the end of the ssDNA tail escapes from the constriction altogether. By considering the length of DNA(19) and the total size of the MspA pore(6, 20), L domain is set to be the length of 14 nucleotides, with length per base a 0 =0.5nm. According to the first-passage approach, we define the probability of passage times as f esc ( x 0 , t ) dt , which represents the probability that the DNA escapes from the pore back into solution within a time between t and t + dt, given an initial starting position x 0 .…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, close inspection of the Mtb cell surface reveals the formation of MAD1 cylindrical assemblies that are ~14 nm in diameter (Figure 4d, magnified image and inset), which approximates the size of the MspA porin head (9 nm in width). 31 TEM images shown in Fig. 4e demonstrate that at low MAD1 concentrations (0.1 x MIC) cytoplasmic granules begin to develop, which are indicative of an early cellular stress response.…”
Section: Mtb-instructed Mad1 Assembly Into Supramolecular Nano-lyticsmentioning
confidence: 90%
“…The zeta potential  of MspA vesicles has been reported and discussed in an earlier report. 20 In 1X PBS, the  value of MspA is slightly positive ( = 10 ± 14 mV)in the low temperature range (296 to 320 K). Above 320 K, a remarkable increase of  to 100 ± 12 mV at 344 K is observed.…”
Section: Temperaturementioning
confidence: 93%
“…We also investigated the aggregation of individual MspA 20 and RuC2/MspA mixtures in dilute 1x PBS aqueous solutions as a function of temperature by using dynamic light scattering. 21 In a previous report, we showed that MspA has a distinct tendency to aggregate with increasing temperature, 20 and the maximum diameter of the MspA vesicles was ~180 nm at 312 K. We established that MspA aggregation proceeds due to hydrophobic interactions between the docking zones of the proteins (see Figure 1a). Although hydrophobic interaction is the major mechanism behind the aggregation behavior of MspA, we also found evidence of contributions from hydrogen bonding and/or ionic interactions to the supramolecular behavior of MspA.…”
Section: Aggregation Of Mspa and Ruc2 By Dynamic Light Scatteringmentioning
confidence: 99%